Development of Active Biocomposite Films Based on Poly(Lactic Acid) and Wine By-Product: Effect of Grape Pomace Content and Extrusion Temperature - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Muñoz-Shuguli, C (John Wiley and Sons Inc, 2023)
This work aims to evaluate the effect of the extrusion temperature of poly(lactic acid) (PLA) with different grape pomace (GP) content for the development of active biocomposite films. Two different GP concentrations (10 and 15 wt.%) were used to obtain GP/PLA composites through extrusion at three different temperature profiles. The biocomposites were characterized through optical, thermal, structural, and mechanical tests. In addition, the antimicrobial and antioxidant capacity of materials were evaluated. Results showed GP antioxidant components are stable up to 180°C. The incorporation of GP in PLA resulted in red-color films with a high color difference (ΔE > 30). The glass transition, cold crystallization, and melting temperatures as well as the tensile strength of PLA decreased by increasing GP concentration in the films; however, elastic modulus and elongation at break increased. The biocomposite with lowest GP content had better antimicrobial activity against Escherichia coli and Listeria innocua. Contrary, 15% GP/PLA composite showed the highest antioxidant activity. Nevertheless, high extrusion temperature profile reduced the bioactivity of materials due to the GP degradation. These results showed the feasibility and best extrusion temperature profile to develop active materials using wine by-products, which could be applied as active food packaging. © 2023 Wiley Periodicals LLC.